Faktor-Faktor Yang Mempengaruhi Kepemilikan Jaminan Kesehatan Pada Rumah Tangga di Sumatera Barat - Ardila Putri; Ariusni Ariusni (Universitas Negeri Padang, 2023)
This study aims to analyze the factors that influence the ownership of healthinsurance in households in West Sumatra. The variables used in this studywere health insurance ownership, area of residence, marital status, gender,age, education level, business field, health complaints, and household percapita expenditure. The data used in this study is Susenas data in 2020. Whilethe analytical method used in this study uses Logistics Regression analysis.The results of this study indicate that 75.45% of household heads already havehealth insurance. The factors that influence the ownership of health insurancein households in West Sumatra are the area of residence, marital status,gender, age, education level, and household expenditure per capita. While thevariables of business field and health complaints do not affect the ownershipof health insurance inhouseholds.